Changes in selected biochemical indices related to transport of broilers to slaughterhouse under different ambient temperatures - Vosmerova, P; Chloupek, J; Bedanova, I; Chloupek, P; Kruzikova, K; Blahova, J; Vecerek, V (Poultry science, 2010)
The effect of transport distance on selected biochemical parameters (corticosterone, uric acid, triglycerides, total protein, glucose, and lactate) under various ambient temperatures was monitored in a group of unsexed Ross 308 broilers aged 42 d. Broilers were transported to the slaughterhouse over 3 different travel distances (10, 70, and 130 km). They were sampled before and after each transportation in 3 various periods with different ambient temperatures (-5 to +5°C, 10 to 20°C, and 25 to 35°C), which approximately correspond to temperature conditions during transport in individual seasons of the year (winter, fall, summer). The changes in biochemical parameters were specific in their dependence on the travel distance and the ambient temperature under which the broilers were transported. The highest corticosterone concentration was found in broilers before transport (i.e., immediately after catching, crating, and loading) at all ambient temperatures. The concentration of corticosterone was higher at winter temperatures than at summer and fall temperatures. Triglycerides decreased with travel distance, although this effect was detected under summer temperatures only. The concentration of total protein was higher only after 10 km of transport and then it decreased with travel distance at all monitored ambient temperatures. A highly significant decrease (P < 0.01) in the glucose level of broilers was observed after 130 km of transport when compared with broilers before transport at fall and winter temperatures. The effect of travel distance on lactate concentrations was the same at all monitored ambient temperatures, with the lactate level decreasing with travel distance. The results obtained indicate that pretransport handling procedures (catching, crating, and loading) may be more stressful for broilers than the transport itself. To improve broiler meat quality, it is necessary to meet the need for broilers to recover before being slaughtered. With regard to different seasons of the year, we can assume that transport under conditions of low ambient temperatures in winter represents a more stressful event than transport during fall and summer.
Keywords: kur domácí; Temperature; kyselina močová; Chickens; Corticosterone; psychický stres; Transportation; doprava; Uric Acid; triglyceridy; Animals; kortikosteron; jatka; Travel; cestování; Stress, Psychological; zvířata; Abattoirs; teplota; Triglycerides